36 SQUAMOUS CELL CARCINOMA OF THE LUNG PRESENTING AS ABDOMINAL PAIN. (1st January 2006) - Jayawardena, S.; Akinyemi, E.; Sridhar, S.
Abstract : Introduction: Lung cancer is the most common cause of mortality in the United States. Most squamous cell carcinomas are central lesions with hilar and mediastinal lymph node involvement. Squamous cell carcinoma has the best prognosis among lung cancers. Case Report: A 67-year-old male presented with symptoms of left-sided abdominal pain for 3 days. The patient denied having altered bowel habit, loss of weight, loss of appetite, or other constitutional symptoms. He was a chronic active smoker and had a history of diabetes mellitus type II and hypertension. On examination the patient was febrile with a temperature of 1008F, decreased air entry in the right lower lobe of the lung, and tenderness in the left lower quadrant of the abdomen with no guarding or rigidity. Stool guaiac was negative. Initial chest x-ray showed an infiltrate in the right lower lobe of the lung; CT with contrast of the abdomen showed multiple lesions in the liver and thickening of the sigmoid colon. CT of the chest and transbronchial and transthoracic biopsies of the lung revealed peripheral cavitatory squamous cell carcinoma without hilar or mediastinal adenopathy. Subsequent colonoscopy and biopsy revealed metastasis to the colon. The patient also had hypercalcemia and leukocytosis. Discussion: The chest x-ray and CT scan in our patient showed a mixed-density pleural-based lesion in the right lower lobe and purulent material obtained on CT-guided biopsy revealed squamous cell carcinoma with extensive coagulation necrosis. The most common carcinoma associated with a cavitating metastasis is squamous cell carcinoma. Compared to solid squamous cell carcinoma, cavitating squamous cell carcinomas are more aggressive, more chemoresistant, and associated with a poorer prognosis. Squamous cell carcinoma can metastasis to the bowel; however, this is very rare. Our patient had persistent hypercalcemia and leukocytosis. Both of these have been associated with various malignancies, including lung cancer as part of the paraneoplastic syndrome either independently or very rarely together. Conclusion: Lung cancer continues to present in advanced stages with unusual metastases. The presence of leukocytosis-hypercalcemia syndrome compounds the already poor prognosis of advanced metastases in our patient. In patients with risk factors such as smoking a high degree of suspicion should be there to detect unusual presentation of lung cancer.